Detection of peptidic erythropoiesis-stimulating agents in sport - Reichel, C. (British Journal of Sports Medicine, 2014)
- Detection methods for erythropoiesis-stimulating agents in sport can be classified into direct and indirect approaches. Direct methods comprise electrophoretic techniques (isoelectric focusing (IEF-), sodium-dodecylsulfate (SDS-), sarcosyl (SAR-) polyacrylamide gel-electrophoreses (-PAGE)), ELISAs and mass spectrometric methods. The haematological module of the Athlete Biological Passport is currently the only applied indirect approach. Newer developments include a mass spectrometric test for peginesatide, sequential exoglycosidase digestion of ertythropoietin (EPO) combined with electrophoresis (SDS/SAR-PAGE), a dipstick method (MAIIA), and a study on the differences in sialic acid O-acetylation of tryptic EPO O-glycopeptides. The focus of this article is on direct detection methods.